Beyond averages: dissecting urban-rural disparities in skilled antenatal care utilization in Bangladesh - a conway-maxwell-poisson regression analysis - Md. Muddasir Hossain Akib; Farzana Afroz; Bikash Pal (BMC Pregnancy and Childbirth)
Abstract Background Taking a sufficient number of skilled antenatal care (SANC) visits is incontrovertibly connected to safe motherhood. This study aims to shed light on the prevalence and potential factors associated with disparities in the SANC taking behavior of pregnant mothers in rural and urban Bangladesh. Methods For this purpose, a nationally representative secondary dataset from the Bangladesh Demographic and Health Survey (BDHS, 2017-18) has been considered. The information regarding the last birth of mothers who delivered within three years preceding the survey has been analyzed. We have applied the Conway-Maxwell-Poisson regression model (CMPRM) to deal with the overdispersion in skilled ANC count data, as this model shows the least AIC compared to the classical negative-binomial regression model (NBRM) and the generalized Poisson regression model (GPRM). Results Significant disparity (p-value < 0.001) has been observed in the mean number of SANC taken by rural (3.17) and urban (4.52) women. The analysis revealed that covariates have significantly different effects on SANC visits in rural areas compared to urban areas. For instance, women aged 35 and above in rural settings exhibited a 37% higher incidence rate of SANC visits (IRR = 1.37) compared to those under 20. Educational attainment had a pronounced impact, with rural women showing a 39% (IRR = 1.39) increase in SANC visits for primary education, 57% (IRR = 1.57) for secondary education, and 64% (IRR = 1.64) for higher education, compared to uneducated women. In contrast, in urban areas, higher education resulted in only a 35% (IRR = 1.35) increase. Conclusion Our findings from this study indicate that the concerned authority should come forward, and policymakers should emphasize various factors that are mainly responsible for the noteworthy different SANC status of pregnant women living in rural and urban areas in Bangladesh. Doing so, it can be hoped that the required number of ANC visits (eight or more) in both types of residences in Bangladesh, recommended by the World Health Organization (WHO), will be satisfied to ensure safer motherhood.